Comparative Study of Clevidipine to Nicardipine for Perioperative Hypertension in Patients Undergoing Cardiac Surgery. (June 2023) - Colomy, Veronika V.; Reinaker, Travis S.
Objective: The primary objective of this study was to compare the efficacy of clevidipine to nicardipine in the treatment of perioperative acute hypertension in patients undergoing cardiac surgery.Methods: This was a single-center retrospective study which included patients who received either clevidipine or nicardipine. Patients were followed for the duration of study drug infusion or for a maximum of 48 hours. Outcomes assessed included the percent of time spent within patient specific goal blood pressure, incidence of hypertensive events per patient, safety outcomes, and cost of medication treatment.Results: There were 201 cardiac surgeries performed between August 2018–January 2019 and July 2019–February 2020. Sixty-seven patients met our inclusion criteria of receiving either clevidipine (n = 29) or nicardipine (n = 38). The median percent of time spent within goal blood pressure range for clevidipine was 55.2% compared to 36.4% for nicardipine treatment ( P = .036). The median number of hypertensive episodes per patient was 3 for clevidipine and 2 for nicardipine ( P = .211). There were no identified differences in safety outcomes such as hypotension, vasopressor use, serum creatinine elevation, tachycardia, and atrial fibrillation. The median cost of treatment required for the observed 48-hour period with clevidipine was 128.58 compared to 55.74 for nicardipine ( P < .001).Conclusion: Our findings suggest that patients undergoing cardiac surgery on clevidipine had better perioperative blood pressure control compared to nicardipine, with a negligible increase in cost, and no observed difference in safety.